2012
DOI: 10.12693/aphyspola.122.497
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Characterization of Hot Tearing Curves Recorded during Solidification of Magnesium Alloys

Abstract: This work investigates the hot tearing behavior of MgAl and MgZn alloys quantitatively based on the measurement of contraction force using an experimental setup which was developed at MagIC. An emphasis is given on the analysis of typical hot tearing curves to understand the corresponding metallurgical phenomena shown by these curves. The recorded hot tearing curves, i.e. the contraction force vs. temperature or time, contain valuable metallurgical information. They give not only the precise temperature at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…After hot tears occur, the neighbouring regions have a negative pressure. The negative pressure can suck back the eutectic liquid, and subsequently heal the hot cracks [39]. Liquid healing was reported for Mg-Y and Mg-Gd binary alloys, especially at a high solute content [7,15].…”
Section: Effect Of Zn Additionmentioning
confidence: 99%
“…After hot tears occur, the neighbouring regions have a negative pressure. The negative pressure can suck back the eutectic liquid, and subsequently heal the hot cracks [39]. Liquid healing was reported for Mg-Y and Mg-Gd binary alloys, especially at a high solute content [7,15].…”
Section: Effect Of Zn Additionmentioning
confidence: 99%
“…However, the analysis of the castings (shown in the next section) indicates that hot tearing occurred in this alloy too. In this situation, according to Huang et al [30], the onset of hot tearing can be identified by locating the point at which the load as a function of time changes from linear increment to non-linear increment in the force curve. Hence the initiation temperature of hot tearing for Mg-1.5 wt.% Y alloy is found to be 616.6 °C .…”
Section: Hot Tearing Volume Measurementmentioning
confidence: 99%
“…At last, the eutectic is formed from the last remaining liquid at eutectic temperature and appears as eutectic segregation on the SEM micrograph [37]. Many previous investigations have shown that the eutectic liquid can completely or partially heal the previously formed hot cracks in binary Al-Cu [37,38], Mg-Al, Mg-Zn and Mg-Y alloys [9,39]. In direct chill casting of Al-Cu binary alloys, a thick line of eutectic (or eutectic path) along grain boundaries of several grains is observed near the tear region [37,38].…”
Section: Effect Of Zn Additionmentioning
confidence: 99%